Readiness Analysis of Recommendation System for Digital-Based Clinic Operations in Nganjuk District - Sentot Imam Suprapto; Andriyana Maharani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Licensing services provided by the government to the community ideally facilitate the community in its implementation. However, many people still complain about the current state of public services. Licensing services as a form of public service are still considered by the community to be too complicated in applying for permits, because of the many procedures that must be passed so that it takes a long time. The purpose of this research is to exploreanalysis of the readiness of a digital-based clinical operating permit recommendation system in Nganjuk Regency. The design of this study is a qualitative research with a phenomenological approach with the focus of the research directed at exploring the analysis of the readiness of a digital-based clinic operating permit recommendation system in Nganjuk Regency by triangulation. In addition, with a qualitative approach, it is hoped that the situation and problems encountered in these activities can be disclosed. The readiness of the community, especially for those who want to establish clinics and clinic owners in welcoming the application of the recommendation for a digital-based clinic operating permit, is quite good. Where the community is enthusiastic about this program, it can be realized immediately where this digital-based system can make it easier for individuals to apply for a clinic operating permit. Apart from the individual aspect, it is also necessary to prepare education or publication in the form of audio-visual related procedures for conducting digital-based operational permits, as well as related agencies must prepare the system as well as possible. Informants are expected to welcome this digital-based clinic operational permit recommendation program with high enthusiasm and it is hoped that if it is implemented in the future, it will be able to implement it properly and at the same time provide constructive criticism if the program still has shortcomings.